2009
DOI: 10.1183/09031936.00059009
|View full text |Cite
|
Sign up to set email alerts
|

Absorptive clearance of DTPA as an aerosol-based biomarker in the cystic fibrosis airway

Abstract: Biomarkers providing in vivo quantification of the basic elements of cystic fibrosis (CF) lung disease are needed. A study was performed to determine whether the absorption of a small radiolabelled hydrophilic molecule (Indium-111 (In-)DTPA) would be increased in CF airways. DTPA clearance has been used previously to assess epithelial permeability and may also be useful for quantifying liquid absorption.The absorptive clearance rate of DTPA was quantified in 10 CF and 11 control subjects using a novel aerosol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
4
13
0
Order By: Relevance
“…In the current study, MCC and DTPA absorption were measured in vivo using dual-isotope ( 99m Tc-SC and 111 In-DTPA) imaging. While statistically significant differences in baseline MCC were not detected between study groups, DTPA absorption was found to be increased in CF patients, consistent with our previous in vivo [11] and in vitro [10] results. These findings were similar in central zone measurements and when data were analysed using the AAC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, MCC and DTPA absorption were measured in vivo using dual-isotope ( 99m Tc-SC and 111 In-DTPA) imaging. While statistically significant differences in baseline MCC were not detected between study groups, DTPA absorption was found to be increased in CF patients, consistent with our previous in vivo [11] and in vitro [10] results. These findings were similar in central zone measurements and when data were analysed using the AAC.…”
Section: Discussionsupporting
confidence: 91%
“…Previous in vitro results from our laboratory have shown that the absorption rate of radiolabelled DTPA is: 1) increased in CF HBE cell cultures compared with non-CF cell cultures; 2) well correlated with the ASL absorption rate; and 3) influenced by transepithelial osmotic gradients [10]. In vivo , we have previously shown that the absorptive clearance of DTPA is increased in the lungs of CF subjects compared with healthy volunteers [11]. Taken together, these results support the hypothesis that DTPA absorption correlates with transepithelial liquid absorption.…”
Section: Introductionmentioning
confidence: 97%
“…Tc-SC is only cleared by MCC while In-DTPA is cleared by both MCC and absorption. Subtracting the MCC clearance rate from the total DTPA clearance rate provides an estimate of the absorptive component of DTPA clearance (ABS) [10, 12, 13]. Studies in epithelial cell cultures have demonstrated proportional relationships between ABS and ASL absorption.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements of mucociliary clearance (MCC) using nuclear imaging techniques are used in CF therapeutics development [59]. Our center has developed a variation of this technique that includes a parallel measurement of small molecule absorption (ABS) [1013]. In vitro studies have demonstrated a proportional relationship between ABS and ASL absorption rate [11].…”
Section: Introductionmentioning
confidence: 99%
“…Retention of Tc-SC, which is a metric of MCC, is shown with model fit for each patient group in Figure 3 [3]. Data from pediatric patients with CF and healthy controls who inhaled isotonic saline is also shown.…”
Section: Resultsmentioning
confidence: 99%